2015
DOI: 10.1136/bcr-2015-212216
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide-related adrenal insufficiency

Abstract: Iatrogenic adrenal insufficiency is a potential harmful side effect of treatment with corticosteroids. It manifests itself when an insufficient cortisol response to biological stress leads to an Addisonian crisis: a life-threatening situation. We describe a case of a patient who developed an Addisonian crisis after inappropriate discontinuation of budesonide (a topical steroid used in Crohn's disease) treatment. Iatrogenic adrenal insufficiency due to budesonide use has been rarely reported. Prescribers should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…In particular, estrogens and oral contraceptives or creams containing testosterone or estrogens can cause an early closure of the growth plate. Similarly, an excessive intake of foods containing phytoestrogens such as soya, according to some studies, may have an effect on bone age progression (56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Endocrine and Nonendocrine Causesmentioning
confidence: 99%
“…In particular, estrogens and oral contraceptives or creams containing testosterone or estrogens can cause an early closure of the growth plate. Similarly, an excessive intake of foods containing phytoestrogens such as soya, according to some studies, may have an effect on bone age progression (56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Endocrine and Nonendocrine Causesmentioning
confidence: 99%
“…However, inhaled drugs reach systemic circulation either by direct absorption through the lungs or via gastrointestinal absorption of the drug when it is inadvertently swallowed [19,20]. It was reported that budesonide triggers several chronic impairment effects, such as oxidative stress, cellular transformation, tissue fibrillation and adrenal insufficiency [14,21]. However, there have been no studies of the effects of inhaled budesonide or salbutamol on metabolic derangements.…”
mentioning
confidence: 99%
“…The metabolic effects of budesonide are mediated through its binding to the glucocorticoid receptor, which is ubiquitously expressed in the human body. Upon ligand binding, the glucocorticoid receptor translocates into the nucleus, where it enables the initiation or suppression of metabolism-related gene transcription [12][13][14]. Salbutamol is also widely used as a relatively selective b2-adrenergic bronchodilator for the relief of acute asthma symptoms [15].…”
mentioning
confidence: 99%
“…Oral budesonide, frequently used to treat inflammatory bowel disease, undergoes extensive inactivation during first pass metabolism. However, the drug can be absorbed systemically and cases of adrenal crisis and Cushing’s syndrome have been reported following prolonged use 112113. Patients who are taking higher doses of oral budesonide (eg, >6 mg) for more than eight weeks and those on long term treatment (regardless of the dose used) should be considered at higher risk of GI-AI 114115116117.…”
Section: Factors Affecting Likelihood Of Glucocorticoid Induced Adrenal Insufficiencymentioning
confidence: 99%